Post Partum Death in a Patient Diagnosed With COVID-19 - Sivevski, Atanas; Karadzova, Dafina; Davceva, Natasha; Aleksioska-Papestiev, Irena; Kadriu, Romir; Velickovic, Ivan; Markovic, Ivana; Pejcic, Nada; Baysinger, Curtis L. (Frontiers in Global Women's Health, 2020)
INTRODUCTION: There are few case reports describing maternal mortality and intensive care of the pregnant patient with COVID-19 infection. CASE: A 27-year-old patient at 34 weeks of gestation was admitted for the evaluation of cough, fever, tachypnea, and oligohydramnios. The day of admission she underwent cesarean delivery for a non-reassuring fetal heart rate tracing and the potential for rapid respiratory decompensation. Over the next 6 days her clinical condition deteriorated, she developed multi organ system failure, and died despite aggressive supportive care. CONCLUSION: Mortality in the pregnant women with COVID-19 infection is infrequently reported and the clinical course leading to death can be progressive over days despite aggressive supportive care. Management strategies specific for the pregnant women have not been developed. Vertical transmission of infection to the neonate did not occur in our case and has not been demonstrated in other pregnancies with COVID-19 disease.